2006
DOI: 10.1159/000087306
|View full text |Cite
|
Sign up to set email alerts
|

Venobronchial Fistula: An Unusual Complication of Long-Term Central Venous Access

Abstract: A venobronchial fistula developed between the azygous vein and the upper aspect of the right main bronchus 12 months after completion of the treatment of a stage IIIB non-small-cell lung cancer in a 54-year-old man. The fistula contained the tip of the catheter placed for chemotherapy perfusion. The reported case presented risk factors previously identified for such a complication. In addition, some clinical particularities were present, suggesting new potent risk factors and some preventive means for safe lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Venous-bronchial fistula is an extremely rare finding and often caused by long-term central venous catheters (CVCs). [ 1 ] The possible mechanism is friction between the catheter tip and vessel wall by withdrawing blood or by vessel wall irritation with chemotherapy or hyperalimentation agents. [ 2 3 4 ] Malposition of CVC in the azygos vein is another reportable cause of fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Venous-bronchial fistula is an extremely rare finding and often caused by long-term central venous catheters (CVCs). [ 1 ] The possible mechanism is friction between the catheter tip and vessel wall by withdrawing blood or by vessel wall irritation with chemotherapy or hyperalimentation agents. [ 2 3 4 ] Malposition of CVC in the azygos vein is another reportable cause of fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal placement of the tip is in the SVC or upper right atrium [4]. Complications associated with central venous lines can include mechanical and chemical injury to the vessel wall with thrombus formation [4,5], development of a fibrin sheath around the central venous line tip [5], venobronchial fistula [6], infection [7], and misplacement or migration into other vessels, including the azygos vein. In one study, investigators found azygos malposition in 0.7% of central venous lines [8]; in another study, the rate was 1.2% [9].…”
Section: Discussionmentioning
confidence: 99%
“…Management demands a group (pulmonologist, cardiothoracic surgeon, interventional radiology/nephrology) consensus to be taken. The perforating catheter segment if situated proximally can be removed by bronchoscopy (endoluminal section of the tip) with subsequent placement of a stent (6) or removed during thoracotomy. Keeping in mind the possibility of hemoptysis, the catheter maybe removed (nonsurgically) in an operating room with the patient lying on the ipsilateral side to prevent blood entering the contralateral lung (7) or using a Fogarty bronchial occlusion catheter to cordon off the bleeding (4).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features with regard to catheter tip embolization have ranged from being asymptomatic to development of various complications (discussed later). Venobronchial perforations have occurred predominantly with left‐sided central venous catheters (CVCs) (4–8). Clinical features include cough, chest pain, dyspnea, hypoxemia, pneumonitis, and a peculiarly unpleasant odor if medication is given at the time of symptoms through the catheter (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation